2020
DOI: 10.1145/3386089
|View full text |Cite
|
Sign up to set email alerts
|

Ordinary User Experiences at Work

Abstract: We investigate professional greenhouse growers' user experience (UX) when using climatemanagement systems in their daily work. We build on the literature on UX, in particular UX at work, and extend it to ordinary UX at work. In a ten-day diary study, we collected data with a general UX instrument (AttrakDiff), a domain-specific instrument, and interviews. We find that AttrakDiff is valid at work; its threefactor structure of pragmatic quality, hedonic identification quality, and hedonic stimulation quality is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 100 publications
(159 reference statements)
0
1
0
Order By: Relevance
“…As mentioned in section 3.1, the effect of HQI on ATT was about twice times compared to HQS, and it was not substantially different compared to PQ. The strong effect of HQI on ATT is in contrast with a previous study of UX at work (Clemmensen, Hertzum and Abdelnour-Nocera, 2020), which reports PQ had the stronger effect on ATT. Although authors hypothesised that PQ would have a stronger effect on ATT, they identified that the three AttrakDiff factors had similar effects on ATT (Schrepp, Held and Laugwitz, 2006).…”
Section: Capturing Multidimensional Ux With Attrakdiffcontrasting
confidence: 99%
See 3 more Smart Citations
“…As mentioned in section 3.1, the effect of HQI on ATT was about twice times compared to HQS, and it was not substantially different compared to PQ. The strong effect of HQI on ATT is in contrast with a previous study of UX at work (Clemmensen, Hertzum and Abdelnour-Nocera, 2020), which reports PQ had the stronger effect on ATT. Although authors hypothesised that PQ would have a stronger effect on ATT, they identified that the three AttrakDiff factors had similar effects on ATT (Schrepp, Held and Laugwitz, 2006).…”
Section: Capturing Multidimensional Ux With Attrakdiffcontrasting
confidence: 99%
“…However, despite the availability of numerous mHealth apps, their uptake among healthcare workers (HCWs) after download remains limited (Medhanyie et al, 2015). This is primarily due to poor user experience (UX), along with the challenge of integrating the app into HCWs' every-day working situations (Kujala et al, 2011;Clemmensen, Hertzum and Abdelnour-Nocera, 2020). User exp in the workplace, also known as UX at work, plays a critical role in determining the success of individuals' everyday use of work-place systems (Lu and Roto, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a sense, everyday automation is thus a strong driver for putting into practice the visions of "ubiquitous computing" [58,73], the "disappearing computer" [66], as well as ambient intelligence [10]. The ambient nature of automated systems and their interwovenness in mundane, repetitive routines also supports the ordinariness of the involved user experience [11,40]. Modern building management systems are a good example for underlying automation that frees users from complexity, but that can also be intransparent [1].…”
Section: Implicit Interactionmentioning
confidence: 99%